Nuklearmedizinische und radiologische Diagnostik und Therapie der Schilddrüsenerkrankungen: Teil 1:Benigne Erkrankungen der Schilddrüse - Zechmann, Christian; Haufe, Sabine (Der Radiologe, 2012)
The thyroid gland is one of the most important endocrine organs. It has multiple influences on physical and mental health. The most important benign diseases are goiter, thyroid adenomas and inflammation. The clinical, imaging and laboratory findings are often pathognomic. The therapy spectrum ranges from follow-up, to medication or definitive therapy by operation or radioiodine therapy.